MENINGKATKAN HASIL BELAJAR MATEMATIKA MENGGUNAKAN MODEL PEMBELAJARAN MISSOURI MATHEMATIC PROJECT SISWA KELAS VIII SMPN 14 MERANGIN - Yohanes (Pendidikan Matematika | STKIP YM Bangko, 2019)
The purpose of this study is to describe an increase in mathematics learning outcomes in the material building of flat-side space using the Missouri Mathematic Project Learning Model in class VIII of SMP Negeri 14 Merangin Academic Year 2018/2019. This research is a classroom action research which consists of four stages, namely planning, action, observation and reflection carried out in SMP N 14 Merangin with the research subjects are all students of class VIII D SMP N 14 Merangin Academic Year 2018/2019, amounting to 28 people . The study was conducted in two cycles, each cycle consisting of III meetings. Data is collected using observation and evaluation, observations in the form of student activity sheets, for evaluation of learning outcomes tests in the form of essay form test questions. Data analysis techniques use simple statistics. The results of the study show that the Missouri Mathematic Project Learning Model can improve student learning outcomes and the average value of students 68.83 in the first cycle to 88.36 in the second cycle. Increased student mastery learning in the first cycle is 14 students or 50% increased in the second cycle to 26 students or 88.7%. Thus the completeness of student learning outcomes has reached more than ≥ 70.00. Based on the results of this study, it is expected that teachers can be used to add models in learning so as to improve the ability of students in learning. Keywords: Mathematics Learning, Aptitude Learning Model Treatment Interaction (ATI), and learning outcomes